C# 8 quick syntax reference : a pocket guide to the language, APIs, and library - Olsson, Mikael (Web programmer) (Apress Media, LLC, 2020)
This quick C# 8 guide is a condensed code and syntax reference to the C# programming language, updated with the latest features of C# 8 for .NET and Windows 10. This book presents the essential C# 8 syntax in a well-organized format that can be used as a handy reference. Specifically, it covers nullable reference types, async streams, ranges and indices, default implementations of interface members, recursive patterns, switch expressions, target-typed new-expressions, platform dependencies and more. In the C# 8 Quick Syntax Reference, you will find a concise reference to the C# language syntax: short, simple, and focused code examples; a well laid out table of contents; and a comprehensive index allowing easy review. You won't find any technical jargon, bloated samples, drawn-out history lessons, or witty stories. What you will find is a language reference that is to the point and highly accessible. The book is packed with useful information and is a must-have for any C# programmer. What You Will Learn Discover what's new in C# 8 and .NET for Windows 10 programming Employ nullable reference types Explore the advanced async streams now available in C# 8 Work with ranges and indices Apply recursive patterns to your applications Use switch expressions Who This Book Is For Those with some experience in programming, looking for a quick, handy reference. Some C# or .NET recommended but not necessary.